PENGARUH PENERAPAAN AUDIT SISTEM INFORMASI TERHADAP AUDITOR KINERJA DENGAN PENERAPAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL INTERVENING - Yohan Saputra; Harman Malau (Program Studi Magister Manajemen Universitas Advent Indonesia, 2018)
This study aims to determine the effect of the implementation of audit information system on auditor performance with information technology as intervening variable. The primary data is derived from respondents of around 100 questionnaires to auditors of Bandung public accountants. The sampling method used is purposive sampling,and the analysis used in the study is descriptive analysis, and the analysis methods to test hypotheses is done through path analysis, and correlation coefficients. The results of this study indicate that the application of audit information system, the application of information technology and auditor performance has been done well. The application of audit information system has a significant effect on auditor performance, as well as a significant effect on information technology, but the application of information technology has no significant effect on auditor performance. Furthermore, based on the trajectory coefficient shows that the application of an information system audit has a strong relationship to the auditor's performance while the application of information technology has a weak relationship with the auditor's performance. The application of information system auditing does not have a significant effect on auditor performance with the application of information technology as an intervening variable. This is due to the t-count value is smaller than the t-table value, which is 0.09748051 <2.04227, with a mediation coefficient of 0.125744. This means that the presence of technology as a mediation of the application of information system audits does not significantly influence auditor performance.